ANALISIS KADAR LOGAM NIKEL DALAM BAKTERI SIMBION PADA SPONS Xestospongia sp - Alfian Noor; Maming Gaffar (Marina Chimica Acta, 2013)
This study aims to analyze the levels of nickel in bacterial symbionts of sponge, inside and outside of bacteria. Bacteria coccus and bacillus were isolated and identified from the sponge Xestospongia sp. The results of analysis using ICP-OES (Inductively Couple Plasma-Optical Emisión Spectrometry) showed that nickel metal content of bacterial symbionts Xestospongia sp sponge in outer island Barrang Lompo were : the initial isolates of 0.7073 ppm and 0.1860 ppm at the end of the isolates while nickel assays for bacterial part in the initial isolates was 0.8763 ppm and 0.2262 ppm at the end of the isolates.